2021
DOI: 10.1038/s41467-020-20275-0
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically potent and selective clusterzymes for modulation of neuroinflammation through single-atom substitutions

Abstract: Emerging artificial enzymes with reprogrammed and augmented catalytic activity and substrate selectivity have long been pursued with sustained efforts. The majority of current candidates have rather poor catalytic activity compared with natural molecules. To tackle this limitation, we design artificial enzymes based on a structurally well-defined Au25 cluster, namely clusterzymes, which are endowed with intrinsic high catalytic activity and selectivity driven by single-atom substitutions with modulated bond le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
184
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 176 publications
(193 citation statements)
references
References 88 publications
8
184
0
1
Order By: Relevance
“…In addition, the zeta potentials of all nanoclusters were around − 35 mV (Fig. 1f), consistent with our previous work [29,49]. These results indicate the ultrasmall size and good colloid stability of nanoclusters, showing the potential in biological applications.…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, the zeta potentials of all nanoclusters were around − 35 mV (Fig. 1f), consistent with our previous work [29,49]. These results indicate the ultrasmall size and good colloid stability of nanoclusters, showing the potential in biological applications.…”
Section: Introductionsupporting
confidence: 91%
“…With the combination of our previous work [29], we concluded that the Au 24 Cd 1 and Au 24 Cu 1 nanoclusters exhibited selectivity on ROS and RNS and showed selective SOD-like and CAT-like activities, which can reduce the oxidative stress induced by brain injury and perform the therapeutic effect (Fig. 4a).…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations